X Międzynarodowy Kongres Archeologii Chrześcijańskiej w Tessalonikach - Longosz, Stanisław (Vox Patrum, 2020)
Report from the Congress of Christian Archeology that took place in Thessaloniki on 28.9-4.10.1980.